Feliks Yakovlevich Kon: chronology of the expedition beyond the Sayan mountains - Neganova, Galina D.; Gantsovskaya, Nina S. (The New Research of Tuva, 2019)
The year 2019 is rich in memorial dates linked to the life and research of Feliks Yakovlevich Kon, a scholar of the history and culture of Tuvans and other peoples. The list of these dates includes 85th anniversary of the publication of his collected works under the title “Za pyatdesyat let” (“In fifty years”, 1934). The third volume of this collection contains his “Expedition to Soyotia”. The book was written on the basis of the materials collected during the Trans-Sayan expedition (to Tuva), which was organized at the behest of the East Siberian Department of the Imperial Russian Geographical Society (ESDIRGS). Researchers have been highly appreciative of the expedition’s outcomes, but little attention has so far been paid to the chronology of the events in the F.Ya. Kon-led expedition.We have reconstructed the order of events from the proceedings and reports drafted by the ESDIRGS, as well as from Kon’s own reports and correspondence. Preparation for the expedition began in spring 1901 and continued until next year. The action plan drafted at this stage was not published until early 1904. The second stage of the expedition took 2 years to complete. The chronology of events in the year 1903 have been reconstructed and classified into periods in accordance with the routes the expedition followed in its second year, between March 27 and August 4, as well as from the phases of stationary work.Our sources do not agree about the time limits of the expedition’s first year. In addition to Kon’s view of the events and his decision to suspend the expedition in March 1902, we also focus on the measures taken by the Steering Committee of the ESDIRGS. The date when the information on Kon’s expedition was actually published in the Russian Anthropological Journal, has also been clarified.The study of the expedition’s chronology helps get a better grasp of the course of studies followed by Kon in his expedition. Its materials being largely of an ethnographic character, they nevertheless are of unique value for linguists, especially those specializing in toponyms and dialects. We believe that the diary of the Trans-Sayan expedition contains important lexicological materials which deserve a dedicated study.
Keywords: Feliks Yakovlevich Kon; Tuva; Soyotia; history of Tuva; scholar of Tuva; “An Expedition to Soyotia”